2020
DOI: 10.1073/pnas.2002707117
|View full text |Cite
|
Sign up to set email alerts
|

Snapping mechanics of the Venus flytrap (Dionaea muscipula)

Abstract: The mechanical principles for fast snapping in the iconic Venus flytrap are not yet fully understood. In this study, we obtained time-resolved strain distributions via three-dimensional digital image correlation (DIC) for the outer and inner trap-lobe surfaces throughout the closing motion. In combination with finite element models, the various possible contributions of the trap tissue layers were investigated with respect to the trap’s movement behavior and the amount of strain required for snapping. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 34 publications
1
83
0
Order By: Relevance
“…These species were selected either being well‐known model species with known triggerable electrical signals (i.e., mechanically triggered signals in D. muscipula [ 49 ] and wounding‐induced electrical responses in A. thaliana [ 13 ] ). Moreover, the species have fast moving organs such as the mechanically snapping trap of D. muscipula [ 49–52 ] and the endogenously oscillating leaves of C. motorius [ 53 ] (both motions occur in relation to electrical signals). Due to their light‐weight, thin‐film structure, and adaptability, the electrodes perform extremely well during challenging measurements on fast moving leaves.…”
Section: Introductionmentioning
confidence: 99%
“…These species were selected either being well‐known model species with known triggerable electrical signals (i.e., mechanically triggered signals in D. muscipula [ 49 ] and wounding‐induced electrical responses in A. thaliana [ 13 ] ). Moreover, the species have fast moving organs such as the mechanically snapping trap of D. muscipula [ 49–52 ] and the endogenously oscillating leaves of C. motorius [ 53 ] (both motions occur in relation to electrical signals). Due to their light‐weight, thin‐film structure, and adaptability, the electrodes perform extremely well during challenging measurements on fast moving leaves.…”
Section: Introductionmentioning
confidence: 99%
“…This snap-buckling part of the movement primarily reflects the conversion of elastic energy into kinetic energy, and hence it is not constrained by hydraulic limitations. A recent study indicated that successful snaping of the trap lobes also requires the previous accumulation of internal hydrostatic pressure and the interplay among three different tissues: the expansion of outer epidermis, the shrinkage of inner epidermis, and the neutral behavior of the middle layer that may function to increase the leverage interaction between the outer and inner epidermises (Sachse et al 2020 ).…”
Section: Movements Of Carnivorous Plants: Beyond the Upper Limit Of Wmentioning
confidence: 99%
“…Typically, these traps catch a single prey per strike [ 48 , 51 ] and can catch additional prey only after resetting. The traps are set by mechanically pre-stressing the trap lobes [ 49 , 52 , 53 ]. Triggering begins with an electrophysiological signalling cascade when mechanosensory trigger hairs on the inside of the trap are bent [ 52 , 54 ].…”
Section: The Trapping Process and Its Energetics For Three Motile Trapsmentioning
confidence: 99%
“…Triggering begins with an electrophysiological signalling cascade when mechanosensory trigger hairs on the inside of the trap are bent [ 52 , 54 ]. In the Venus flytrap, this initiates intrinsically powered turgor changes that cause the trap lobes to deform, initially increasing the concavity of the lobes, until they snap-buckle to become convex, thereby converting mechanical pre-stress into rapid motion [ 53 , 55 , 56 ]. Both lobes move independently of each other, which occasionally results in asynchronous snapping events [ 57 ].…”
Section: The Trapping Process and Its Energetics For Three Motile Trapsmentioning
confidence: 99%